Comorbidity Trends in Patients Requiring Sternectomy and Reconstruction: Updated Data Analysis From 2005 to 2020. (23rd June 2022) - Soto, Edgar; Kumbla, Pallavi A.; Restrepo, Ryan D.; Patel, Jason J.; Davies, James; Aliotta, Rachel; Collawn, Sherry S.; Denney, Brad; Kilic, Ali; Patcha, Prasanth; Grant, John H.; Fix, R. Jobe; et al.
Abstract : Introduction: Comorbidity trends after median sternectomy were studied at our institution by Vasconze et al (Comorbidity trends in patients requiring sternectomy and reconstruction. Ann Plast Surg . 2005;54:5). Although techniques for sternal reconstruction have remained unchanged, the patient population has become more complex in recent years. This study offers insight into changing trends in this patient population. Methods: A retrospective review was performed of patients who underwent median sternectomy followed by flap reconstruction at out institution between 2005 and 2020. Comorbidities, reconstruction method, average laboratory values, and complications were analyzed. Results: A total of 105 patients were identified. Comorbidities noted were diabetes (27%), immunosuppression (16%), hypertension (58%), renal insufficiency (23%), chronic obstructive pulmonary disease (16%), and tobacco utilization (24%). The most common reconstruction methods were omentum (45%) or pectoralis major flaps (34%). Thirty-day mortality rates were 10%, and presence of at least 1 complication was 34% (hematoma, seroma, osteomyelitis, dehiscence, wound infection, flap failure, and graft exposure). Univariate analysis demonstrated that sex ( P = 0.048), renal insufficiency, surgical site complication, wound dehiscence, and flap failure ( P < 0.05) had statistically significant associations with mortality. In addition, body mass index, creatinine, and albumin had a significant univariate association with mortality ( P < 0.05). Conclusions: Similar to the original study, there is an association between renal insufficiency and mortality. However, the mortality rate is decreased to 10%, likely because of improved medical management of patients with increasing comorbidities (80% with greater than one comorbidity). This has led to the increased use of omentum as a first-line option. Subsequent wound dehiscence and flap failure demonstrate an association with mortality, suggesting that increasingly complex patients are requiring a method of reconstruction once used a last resort as a first-line option.